Implementing (un)fair procedures: containing favoritism when unequal outcomes are inevitable [dataset] - Schmidt, Robert J.; Trautmann, Stefan T. (Universität, 2021)
We study the selection of people when unequal payoffs are inevitable, but fair procedures are feasible, as in selecting one person from several can...
Gesehen am 27.10.2021
Keywords: Forschungsdaten; Datenbank